PENGARUH DISIPLIN KERJA DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT KARYA TETANGGA TUKU - M. Caesar Magreza; Laila Irawati (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of work discipline and work training on employee productivity at PT Karya Tetangga Tuku in South Tangerang. This research uses quantitative descriptive methods. The sampling technique used probability sampling and a sample of 89 respondents was obtained. Data analysis techniques use validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The research results of work discipline and work training have a significant effect on work productivity with a coefficient of determination of 31,8%. Meanwhile, the hypothesis test of work discipline on work productivity obtained tcount > ttable or (5,704 > 1,988), and the work training hypothesis test of work productivity obtained tcount > ttable or (4,585 > 1,988). Work discipline and work training simultaneously have a significant effect on work productivity with the regression equation Y = 15,075 + 0,347X1 + 0,268X2. The results of testing work discipline and training on work productivity obtained a calculated F value > F table or (20,071 > 3,100), this shows that there is a significant simultaneous influence between work discipline and work training on work productivity.